Pemanfaatan Tools Canva Dan Template.Net Dalam Pembuatan Sertifikat Online Pada Dinas Pangan Provinsi Aceh - Idwan, Harry; Haikal, M. Hafid; Wali, Muhammad (Jurnal Sistem Komputer (SISKOM), 2024)
This research investigates the use of graphic design tools Canva and the Template.net platform in creating online certificates within the Aceh Province Food Service. With increasingly rapid technological changes, online certificates have become an attractive alternative to increase efficiency and quality in recognizing achievements and contributions. The main focus of this research is to understand the extent to which the use of Canva and Template.net has changed the way certificates are created, as well as identifying benefits, challenges and recommendations for further implementation. This research method combines a qualitative approach with a case study at the Aceh Province Food Service. Data was collected through observation, interviews and analysis of related documents. Content analysis techniques were used to explore key themes that emerged from the data. The research results show that the use of Canva and Template.net has significantly increased efficiency in the certificate creation process. Using these graphic design tools allows Food Service staff to quickly access templates, edit text, and adjust designs as needed. However, several obstacles such as limited accessibility and technical capabilities were also identified. Recommendations from this research include training for staff, development of internal templates, and regular monitoring of application use. This research is expected to provide a deeper understanding of the use of online certificate technology in the Aceh Province Food Service and contribute to increasing efficiency and quality in making certificates.